Indikasi dan Jenis Transplantasi Kornea : Penelitian Retrospektif di RS Mata JEC periode 2014-2018 - Sharita R Siregar; Laura A Djunaedi (Majalah Oftalmologi Indonesia, 2020)
Purpose : Corneal disorders leading to corneal blindness was one of the major causes for blindness worldwide. This retrospective study was done to report the indications for corneal transplantation and also the latest surgical technique between lamellar and penetrating keratoplasty at JEC Hospital, Jakarta Indonesia from 2014 to 2018. Methods : Records of all patients who underwent penetrating and lamellar keratoplasties at our hospital between 2014 and 2018 were reviewed retrospectively. Patient demographic data such as age and gender, together with indications and surgical technique of corneal transplantation were recorded and analysed. Results : Pseudophakic bullous keratopathy, corneal scarring post infection, and corneal dystrophy were the most common indications for corneal transplantation in our centre (33.91%; 28%; 16.63%; respectively). In 2014, corneal ulcer was one of the leading causes for complete corneal transplantation (12.5%) but its incidence was decreasing each year. 66.55% of procedures performed were penetrating keratoplasty. However, the shift from penetrating to lamellar procedures such as DSAEK increases significantly since 2007 and even more increased by 2 times within the last 5 years (15.27%; 35%; respectively). Conclusion : The number of keratoplasties in JEC has increased from 2014 to 2018. Since 2007, posterior lamellar keratoplasties have increased and began to create some shift from penetrating to lamellar since then. There was a constant increase number of DSAEK due to donor availability from the new eye bank in 2017. The shorter recovery time after DSAEK seems to contribute to the trend toward earlier operative intervention in corneal endothelial disease. The leading indications for DSAEK was bullous keratopathy.